Improved T and B cell recovery by the transfer of slowly dividing human hematopoietic stem cells - Vitacolonna, Mario; Schubert, Mario; Herbert, Nicolás; Taubert, Isabel; Singh, Rahul; Ho, Anthony Dick; Zöller, Margot (Leukemia research, 2010)
Human hematopoietic stem cells giving rise to long term initiating cells in vitro are enriched in a CD34+ slow dividing fraction (SDF). Here, we tested reconstitution and multilineage differentiation of this CD34+ SDF in NOD/SCID mice. In the bone marrow a slightly higher percentage of human hematopoietic progenitors were recovered after the transfer of the SDF compared to the fast dividing fraction. Instead, T cell maturation in the rudimentary thymus and lymph node repopulation was only initiated by the SDF. The capacity of the SDF to differentiate and mature in the patients’ thymus could provide an advantage in immunocompetence recovery.
Online veröffentlicht am 10. November 2009
Gesehen am 07.09.2023